PENGIDENTIFIKASIAN SEGMENTASI PENGGUNA SISTEM MANAJEMEN PEMBELAJARAN SEBUAH UNIVERSITAS DENGAN METODE TWO-STEP CLUSTERING - Purnama, Agus Rachmad; Larasati, Aisyah (Journal of Research and Technology, 2020)
This study aims to identify user segmentations of a learning management system at Universitas Negeri Malang using two-step clustering method. Data is collected through an on-line survey which is linked onto the academic information systems. Total number of data are 10.594 responses. This study runs three clustering methods, two-step, k-means, and kohonen clustering, in order to identify the user segmentation. Two-step clustering methods performs better than the other two clustering methods (k-means and kohonen) based on silhouette clustering index. The number of cluster resulted from two-step clustering method are three clusters. The top three of most important factors in identifying the user segmentation are the benefit of the learning management usage in helping to access information, increasing the effectiveness of accomplishing assignments, and students satisfaction on the learning management system services.